A Mini-Review on Power-to-Methane Catalysts - T. Thuy Ha Nguyen; 박은덕 (에너지공학, 2021)
The ever increasing CO2 atmospheric concentration causes the climate change threatening the present and future generations on earth. In order to resolve this global issue, the portion of renewable energy is expected to be increased in near future to replace the conventional fossil fuel-based energy. Because of the variability of renewable energy, various energy storage systems were proposed. One of them is the power-to-fuel concept in which the captured CO2 is hydrogenated into fuels with hydrogen generated through water electrolysis by using renewable electricity. CO2 methanation is one of key steps in this process. Since this is an exothermic reaction and thermodynamically limited one, the development of active catalyst at low temperatures is highly plausible. In this mini-review, we aim to overview the CO2 methanation catalysts which are mainly composed of active metals, supports, and promoters. Furthermore, since CO2 methanation is a highly exothermic reaction and the thermal heat release should be efficiently accomplished, some new concepts for the catalyst and reactor design are also addressed.
Keywords: Power-to-Gas; Catalyst; CO2 methanation; Nickel